Modification of the laser correlation spectrometer for analysis of biological fluids - E.N. Velichko; E.K. Nepomnyashchaya; E.T. Aksenov (Учёные записки Казанского университета: Серия Физико-математические науки)
Modifications of the laser correlation spectrometer system developed for the analysis of biological fluids have been discussed. Parameters of the proposed laser correlation spectrometer allowing to determine the sizes of nanoparticles in biological fluids, which are highly polydisperse solutions, to within 0.5 nm have been presented. We have explained the use of optical fiber in the spectrometer circuit as a system for collecting scattered radiation. Furthermore, we calculated the parameters of the discretization of the registered signals. It is for the correct selection of the ADC-converter. The results of the experiment showing significant differences in the size composition of donor blood serum proteins have been presented. Thus, the possibility for analyzing the composition of the blood serum of various donors and for obtaining diagnostic data has been proved.